Legalizing parents and other caregivers: a family immigration policy guided by a public ethic of care - Sullivan, Michael J.
In this paper, we analyze political debates about headscarves and honor-related crimes in France and the Netherlands. We seek to explain why and how France and the Netherlands have come to unevenly politicize headscarves and honor crimes. Moreover, we try to understand how the argument of gender equality is used by different actors in these policy debates. We argue that the agenda and demands of ethnic minority women′s organizations are selectively included and bent to serve other, non-feminist agendas. Ethnic minority women′s organizations and female ethnic minority politicians have acted as agenda-setters, calling attention to marginalization, discrimination, and experiences of violence. Yet these issues were co-opted by (mainly) right-wing politicians to problematize the “deviant” culture of minorities and propose policies that further exclude them and paternalize them instead of improving their situation.